Amy Eskin and Mitchell Shapson Wedding Reception - Watkins, Howard::::::::: (1988)
Carolyn Murphy (backside), Karen Richardson Gill, Gertrude Miller, Jim Dunny, Louise Richardson, Tom Richardson, Bill Murphy, Ruth Eskin, Diana Householder, Harold Householder, ??? Gertrude is Louise Richardson's mother and Jim Dunny is Louise's brother-in-law